Application of Thermoelectric to Expand Straw Mushroom’s Lifespan Using Internet of Things System: การประยุกต์ใช้เทอร์โมอิเล็กตริกในการยืดอายุเห็ดฟางผ่านระบบอินเทอร์เน็ตของสรรพสิ่ง - Patummakason, Chumpon; Charoensiri, Yosita; Wadsuntud, Kittisak (Advanced Science Journal, 2022)
The objectives of this research were 1) to design and build a straw mushroom storage box using Thermoelectric device and 2) to determine the efficiency of a straw mushroom storage box within Thermoelectric device. In this study, a mushroom storage box has been designed and controlled by the cooling Thermoelectric device, and the humidity has been controlled by the ultrasonic that processed from Node MCU 8266. The Node MCU 8266 can be displayed the values of temperature and humidity via smartphone. The results showed that the mushroom box can be controlled with a stable temperature of 12-13 oC and can be maintain the humidity level at 90-93%. The straw mushroom can be stored last up to 6 days, be fresh as it weighs effectively closed to the harvesting time.